Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 3 - Review: 50

Answer

see graph
1500757501

Work Step by Step

Substituting $y=0$ in the given equation, $ 2x+6y=9 ,$ then \begin{array}{l}\require{cancel} 2x+6(0)=9 \\\\ 2x=9 \\\\ x=\dfrac{9}{2} .\end{array} The $x-$intercept is $\left( \dfrac{9}{2} ,0\right)$. Substituting $x=0$ in the given equation then \begin{array}{l}\require{cancel} 2(0)+6y=9 \\\\ 6y=9 \\\\ y=\dfrac{9}{6} \\\\ y=\dfrac{3}{2} .\end{array} The $y-$intercept is $\left(0, \dfrac{3}{2} \right)$. Using the intercepts, the graph is shown above.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.